A simple model of health insurance competition - Alexander Kemnitz (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2010)
This paper investigates competition between health insurance companies under different financing regulations. We consider two alternatives advanced in recent German health care reform discussions: competition by contribution rates (health contributions) and by fees (health premia). We find that contribution rate competition yields lower company profits and higher consumer welfare than premia competition when switching between insurance companies is costly.
Keywords: I11; I18; D43; 330; Health Care Reform; Competition; Consumer Choice